Insecticidal potential of Ocimum canum plant extracts against Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus larval and adult mosquitoes (Diptera: Culicidae). Issue 10 (18th May 2016) - Murugan, Jimmantiyur Madhappan; Ramkumar, Govindaraju; Shivakumar, Muthugoundar Subramanian
Abstract : Mosquitoes have developed resistance to various synthetic insecticides, making their control increasingly difficult. Insecticides of botanical origin may serve as suitable natural control. This study evaluates the toxic potential of Ocimum canum (Sims) leaf extract and powder against Anopheles stephensi (Liston), Aedes aegypti (Lin) and Culex quinquefasciatus (Say) larval and adult mosquitoes. Larval mortality was observed after 24 h recovery period and adult smoke toxicity observed for 40 min duration at 10 min interval. Methanol extract of O. canum showed highest larval mortality against the larvae of C. quinquefasciatus LC50 = 28.3225, LC90 = 44.1150; Ae. aegypti LC50 = 43.327, LC90 = 61.249; and An. stephensi LC50 = 30.2001, LC90 = 48.2866 ppm. The smoke toxicities were 93% mortality in C. quinquefasciatus, 74% in Ae. aegypti and 79% in An. stephensi adults, respectively, whereas 100% mortality was recorded in the commercial mosquito control. Our results suggest that O. canum leaf extract and powder are natural insecticide, and ideal eco friendly approach for mosquito control. Abstract :